Postlarval development of Halicarcinus planatus (Crustacea, Decapoda, Hymenosomatidae) in the estuary of Deseado River, South Western Atlantic Ocean - Vinuesa, Julio Hector (2008)
This study analyses morphology and morphometric growth changes of Halicarcinus planatus females until their terminal moult, and characterises new juvenile stages. Monthly samples were collected in the estuary of the Deseado River, Santa Cruz Province, Argentina. Crabs were sampled between the mid- intertidal and upper subtidal levels. Intermoult stages were analysed in sub-samples of adolescents and adults, and the presence of epizoic organisms was registered. Juveniles and adults were reared at the laboratory and examined for moult changes. All 3376 crabs caught were females indicating a clear spatial segregation between sexes.  Five juvenile stages (immature 1, 2, 3, 4 and adolescent) and a mature one were recognised on the basis of morphology and morphometry.  All immature stages differed in cephalothorax width (CW) and abdomen width (AW).Positive allometry was observed in some juvenile stages and isometry in an immature stage and in mature females. Adolescents and adults encompassed a wide range of sizes, and the remarkable size overlap between them suggests an anomalous growth process. Moult staging analysis indicated that adolescents presents high incidence of pre- moult stages in winter, when terminal moult occur. The measurements performed in laboratory-reared females indicated no abnormal increases during moult. The terminal moult occurs within a wide size range, maybe in association with mating.